PERANCANGAN SISTEM INFORMASI PENGELOLAAN CATERING HARIAN: (STUDI KASUS : RANTANGAN CIBUBUR) - maulidiah, susi (Journal of Informatics and Advanced Computing (JIAC), 2025)
still done through a spreadsheet application. The process of compiling shopping lists, compiling menus, recapitulation of expenses and income, recapitulation of customer data become less accurate and takes a long time to compile. In this study, the data collection techniques used were observation, interviews and literature studies. The information system designed uses the prototyping method as a software development method using object-oriented design Unified Modeling Language (UML). The process in this study includes the process of recording orders, customer data, cooking menu data, weekly menu data, package data, recapitulation of expenses and income including bills for each customer. The results of the research that have been designed in the design of the daily catering management information system are a system that can compile shopping lists, compile menus, recapitulate expenses and income, recapitulate customer data and periodic reports so that they can be used as evaluation subject to improve daily catering management in the future